EVALUASI INTERVENSI PERAWATAN PALIATIF PADA PENDERITA KANKER TERMINAL DEWASA DI RSUPN DR. CIPTOMANGUNKUSUMO - Putranto R.; Laksono Trisnantoro; Hendra Y. (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Cancer is one of the catastrophic diseases which have the characteristics of high cost, high volume, and high risk. Based on Basic Health Research (Riskesdas) 2013, 65% among 240.000 new cases of advanced cancer per year are seeking medical assistance where the curative treatment no longer effective. Palliative care is an approach that is no longer eradicates the disease, in contrary, it’s an approach to increase the quality of patient’s life until the end of life period (death). Objective: This research aimed to evaluate the correlation of length of stay (LOS) and direct cost of terminal cancer patients who get palliative intervention or not receive palliative intervention. Methods: This study used a retrospective cohort design which involving 120 patients (29 cases and 91 controls) that taken from medical records of hospitalized patient in Cipto Mangunkusumo Hospital (RSCM). The inclusion criteria consist of patient has been diagnosed as terminal cancer disease, aged ≥18 years, and palliative care consultation. Results: The results of the bivariate analysis using Mann- Whitney test showed a significant correlation between direct cost and palliative intervention (p-value = 0,041) and no significant relationship between length of stay (LOS) and palliative intervention (p-value = 0,873). Conclusion: There was a significant relationship between palliative intervention and room expenditure rates, visites, actions, and drugs. Therefore, it’s necessary to further research to explore variables that influence LOS and direct cost in palliative care intervention patients with terminal cancer.